(untitled) (Contemporary Journal of Social Science Review, 2025)
This study examines the interplay between Islamic mysticism (Sufism) and character formulation in Rabisankar Bal’s A Mirrored Life (2015), a fictional exploration of Rumi’s life and teachings. Employing qualitative textual analysis, the paper argues that Bal’s protagonists embody the Sufi concepts of Wahadat al-Wujud (Unity of Existence) and Fanaa (annihilation of the self), which catalyze their spiritual and psychological evolution. By foregrounding Rumi’s metaphysics as a theoretical lens, the study reveals how Bal’s narrative bridges classical Sufi thought and contemporary literary fiction, offering a nuanced portrayal of mystical experiences as transformative forces. The research contributes to two underexplored domains: the representation of Sufi epistemology in modern South Asian literature, and the use of mystical frameworks to interrogate character development beyond Western psychoanalytic paradigms. Ultimately, the paper asserts that A Mirrored Life reframes mysticism not as mystery but as a disciplined pursuit of divine knowledge—a corrective to the term’s neoliberal appropriations in Euro-American scholarship.